THE IMPACT OF THE PRINCIPLE OF SUSTAINABLE DEVELOPMENT ON NUCLEAR LAW: REACHING SUSTAINABILITY TROUGH THE MINIMIZATION OF THE RADIOACTIVE WASTE EXTERNALITY - Apolevič, Jolanta (Teisė, 2015)
In nuclear law the principle of sustainable development is applied either as an ecocentrically-oriented principle, through which it is sought to preserve a sustainable and harmonious environment (e.g., through the requirement that radioactive waste must be handled with particular caution), or as an anthropocentrically-oriented principle, through which it is sought to protect the interests of a human being in implementing the policy of the cautious use of nuclear fuel resources rather than to protect the environment per se. Starting from this point, this article analyses whether the implementation of the ecocentrically-oriented sustainable development principle as well as the application of the environmental legal provisions stemming from this principle to the management of radioactive waste externality is effective in the specific area of nuclear law. The analysis enables to specify the main problems of the relevant legal regulation at the global level, which need to be dealt with in order that nuclear energy could, in an effective way, contribute to sustainable development of natural environment as well as to achieving the aims of environmental protection, with the effects of the ensuing radioactive waste externality being reduced to the minimum. In this respect, the analysis points up the necessity to create international repositories and prepare the legal criteria for their selection and operation, to improve the regulation governing the dumping of radioactive waste at sea, to include radioactive waste from military nuclear reactors within the area of the application of certain appropriate legal acts, to implement the principle of sustainable development at the front-end of the nuclear fuel cycle, i.e., to establish the obligation to submit the information about the waste from uranium mining and milling, which have been regarded as the radioactive waste information. The article concludes with the observation that all the problems related to the implementation of the principle of sustainable development in the area of nuclear law, i.e., the problems of radioactive waste management and fuel conservation, could be overcome, and nuclear energy could be completely sustainable, once an international consensus is reached on adopting the closed fuel cycle, which practically leaves no radioactive waste.